The Treasurers' House
So far had the process of classical design progressed that even the Treasures of reform York Minister built the Renaissance House adjacent to a great Gothic building, completely overlooking the pagan origins of the new work. The next generation was to describe the early centuries of medieval architecture as the Dark Ages and use the word Gothic as a form of contempt. And, before the next century had passed, England was to make her own unique contribution to the new architecture and weld the Elizabethan concept of the English country house to the civilized refinements of the Renaissance.